Reliability and Validity of Two Versions of the Upper Extremity Functional Index - Chesworth, Bert M. (University of Toronto Press Incorporated, 2014)
Purpose: To examine the reliability, validity, and sensitivity to change of the 20-item version and the Rasch-refined 15-item version of the Upper Extremity Functional Index (UEFI-20 and UEFI-15, respectively) and to determine the impact of arm dominance on the positive minimal clinically important difference (pMCID). Methods: Adults with upper-extremity (UE) dysfunction completed the UEFI-20, Upper Extremity Functional Scale (UEFS), Pain Limitation Scale, and Pain Intensity Scale at their initial physiotherapy assessment (Time 1); 24–48 hours later (Time 2); and 3 weeks into treatment or at discharge, whichever came first (Time 3). Demographics, including working status, were obtained at Time 1. Global ratings of change (GRC) were provided by the treating physiotherapist and patient at Time 3. The UEFI-15 was calculated from relevant items in the UEFI-20. The intra-class correlation coefficient (ICC) and minimal detectable change (MDC) quantified test–retest reliability (Time 1–Time 2). Cross-sectional convergent validity was determined by the association (Pearson's r) between Time 1 measures of function and pain. Known-groups validity was evaluated with a one-way ANOVA across three levels of working status. Longitudinal validity was determined by the association (Pearson's r) between function and pain change scores (Time 1–Time 3). Receiver operating characteristic (ROC) curves estimated the pMCID using Time 1–Time 3 change scores and average patient/therapist GRC. Results: Reliability for the UEFI-20 and UEFI-15 was the same (ICC=0.94 for both measures). MDC values were 9.4/80 for the UEFI-20 and 8.8/100 for the UEFI-15. Cross-sectional, known-groups, and longitudinal validity were confirmed for both UEFI measures. pMCID values were 8/80 for the UEFI-20 and 6.7/100 for the UEFI-15; pMCID was higher for people whose non-dominant arm was affected. Conclusions: Both UEFI measures show acceptable reliability and validity. Arm dominance affects pMCID. The UEFI-15 is recommended because it measures only one dimension: UE function.